(untitled) (International journal of artificial intelligence, 2025)
Somatic objects are words and phrases related to parts of the human body. They are often used as metaphors and idioms. For example, in English is used, the expression "keep an eye" or in Uzbek, the phrase "qo’li ochiq" (generous). Such expressions play an important role in reflecting thought processes and cultural values.